Lakuan bahasa pohon maaf dalam bahasa Inggeris oleh penutur dewasa Melayu: pola dan kecekapan (Jurnal Bahasa, 2007)
The speech act of apology has been much researched. Some of the research focused on one culture, while others were cross-culturally compared. However in the Malaysian context, the study of apology has l'et to be ventured, be it to focus its manifestation in the people is. mother tongues, or to focus on how it is manifested in English, an alternative popular language used in the country. This paper is an attempt to explicate the production of apologies in English by adult Malay speakers in Malaysia. The choice for English is made out of the ever mounting effort of the government in encouraging Malaysians to become competent speakers of English, the world's language of wider communication. The choice for apology is due to its popularity as a study of speech acts and being an illocutionary force so common to take place in daily context. The study found that despite years of exposure to English language, the apologies produced displayed influences of the Malay socio-cultural rules.